Kajian Rainbow 2-Connected Pada Graf Eksponensial dan Beberapa Operasi Graf - Herninda Lucky Oktaviana; Ika Hesti Agustin; Dafik Dafik (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2021)
Let $G=(V(G),E(G))$ is a graph connected non-trivial. Rainbow connection is edge coloring on the graph defined as $f:E(G)→ \{1,2,...,r|r \in N\}$, for every two distinct vertices in $G$ have at least one rainbow path. The graph $G$ says rainbow connected if every two vertices are different in $G$ associated with rainbow path. A path $u-v$ in $G$ says rainbow path if there are no two edges in the trajectory of the same color. The edge coloring sisi cause $G$ to be rainbow connected called rainbow coloring. Minimum coloring in a graph $G$ called rainbow connection number which is denoted by $rc(G)$. If the graph $G$ has at least two disjoint rainbow path connecting two distinct vertices in $G$. So graph $G$ is called rainbow 2-connected which is denoted by $rc_2(G)$. The purpose of this research is to determine rainbow 2-connected of some resulting graph operations. This research study rainbow 2-connected on the graph (${C_4}^{K_n}$ and $Wd_{(3,2)}\square K_n$).